Antara Idealisme dan Pragmatisme: Hukum yang Efisien Sebagai Sarana Pembangunan - Prayoga, Reynaldi S (UI Scholars Hub, 2026)
This articles aims to analyze the Development Law Theory through the lens of efficiency in Economic Analysis of Law (EAL), particularly by employing the concept of welfare maximization and offering legal criteria as a means of development. The Development Law Theory formulated by Mochtar Kusumaatmadja emphasizes the function of law as an instrument of social reform to support national development. In practice, however, the will of those in power claimed to be part of the development agenda has often been justified through the use of legal instruments, thereby riskingthe obscuring of social objectives of development itself. This is due to the absence of clear criteria for determining the laws required for development. This researach uses a normative method with a doctrinal and conceptual approach. The study finds that the application of the Development Law Theory as a justification for policy during its time resulted in inefficient law and development, benefiting primarily those in close proximity to political power. Accordingly, the article argues for the necessity of efficent legal framework that actively involve public participation. Keywords: The development law theory, economic analysis of law, efficiency, public participation